Chronicle of a heritage object: The case of the Montevideo Walls - Careaga Alonzo, Adriana (2018)
Since time immemorial, human beings have developed defense strategies for their material goods, which account for the beliefs that sustain them and which, in a certain way, have marked the historical development of their peoples. Therefore, to understand the past of a group of human beingsit is necessary to know the lines of thinking that have developed their defenses. The case study presented below involves the fortified colonial system of the city of Montevideo, more specifically the so-called “land front”, punctually the wall object and its transformation from an invisible object for the community to a national historic monument. We describe the recovery process of a canvas of 13 meters of the wall, located in private land, where an old factory of anilines was operative until the second half of the twentieth century. Through a process of valuation, it became a cultural space called “At the Foot of the Wall” dedicated to heritage education since its opening in 2004, intended for both younger and older generations.